The Painter, His Muse and Their Marriage: George Harvey and Priscilla Wells in Late Victorian Halifax - Yorke, Lois (Journal of the Royal Nova Scotia Historical Society)

(untitled) (Royal Nova Scotia Historical Society, 2025)
George Harvey lingers in our cultural history today only as a footnote, faintly remembered as the first headmaster of Halifax’s new Victoria School of Art and Design in 1887. His wife Priscilla is not remembered at all. Their early lives were lived in bohemian London. Once settled in Halifax, they were well liked and respected, but their local roots ran neither deep nor strong. After the events of 2–3 June 1889 and George Harvey’s subsequent departure from the city six years later, they were briefly subjects of interest, then gradually forgotten. This article revisits their world, reclaims their lives, and gives them the voices they so richly deserve.